Passy muir valve tolerance in medically complex infants and children: Are there predictors for success?. (11th December 2019) - Brooks, Laura; Figueroa, Janet; Edwards, Tracy; Reeder, Walter; McBrayer, Sheila; Landry, April
Abstract : Objective: The aim of this study was to investigate if there are predictors for success with Passy Muir Valve (PMV) placement for medically complex pediatric patients. Methods: Retrospective chart review of 52 pediatric patients with a tracheostomy with or without ventilator dependence who received PMV assessments from October 2017 through October 2018 in intensive care units and acute care units within Children's Healthcare of Atlanta (Atlanta, GA). Univariate analysis and logistic regression modeling were used to identify factors associated with a successful PMV trial. Results: Factors found to be associated with a successful PMV trial were as follows: transtracheal pressure measurement, presence of voicing, age of patient >2 years, weight of patient, and ventilator rate. Conclusion: Medically complex infants and children in the intensive care units and acute care units on or off the ventilator can be considered candidates for PMV use; several factors can be predictive of a successful trial. Level of Evidence: 2C Laryngoscope, 130:E632–E639, 2020